GEOPOLITICAL „DANCE” OF THE AGGRESSIVE DICTATORS - Constantin Mincu (Annals: Series on Military Sciences, 2024)
After studying the geopolitical developments of the last ten years, the author considers, with sufficient arguments, that the subject of this article is of public interest for Romania and its citizens, but also for NATO member states and/or for those of the European Union. The developments on the world stage in the last ten years (after the illegal annexation of Crimea by the Russian Federation) determined mainly by the great nuclear powers (USA, Russia, China), and by some emerging powers (Turkey, Iran, Brazil, India and others), have a potential role in seriously endangering world peace, including the security of European member or non-member states of NATO and/or the EU. I believe that in this complicated and fluid context, Romania must be very careful, determined and focused to counteract, together with the Allies, the military and hybrid risks and threats coming from some state actors with obvious aggressive tendencies.